Characterization of COOH-Fe3O4/NCC-CTA+ on screen printed carbon electrode using Field Emission Scanning Electron Microscope and Energy Dispersive X-Ray for DNA biosensor (Journal of Biochemistry, Microbiology and Biotechnology, 2017)
A novel DNA biosensing platform was designed by the functionalization of iron oxide (Fe3O4)with the carboxylic group via capping agent, mercaptopropionic acid (MPA) and conjugatedwith nanocellulose crystalline (NCC) surface modified with surfactant cetyltrimethylammoniumbromide (CTAB) to assist in the DNA sensing capability. The product of nanocompositescompound was drop-casted on screen printed carbon electrode (SPCE). Characterization by fieldemission scanning electron microscope (FESEM) and energy dispersive X-Ray (EDX)spectroscopy showing that carboxyl functionalized iron oxide (COOH-Fe3O4) can be hybridizedwith NCC-CTA+ via electrostatic interaction.
Keywords: biosensor; DNA; nanocomposite; nanocellulose crystalline; screen printed carbon electrode